3‐D Modeling of Ultrathin Solar Cells with Nanostructured Dielectric Passivation: Case Study of Chalcogenide Solar Cells. Issue 11 (9th September 2021) - Raja, Waseem; Aydin, Erkan; Allen, Thomas G.; De Wolf, Stefaan
Abstract: Ultrathin solar cells can be a path forward to low‐cost photovoltaics due to their reduced material consumption and shorter required deposition times. With excellent surface passivation, such devices may feature higher open‐circuit voltages ( V OC ). However, their short‐circuit current density ( J SC ) may be reduced due to decreased light absorption. This mandates implementation of efficient light‐trapping structures. To design efficient ultrathin solar cells that combine surface‐passivation and light‐trapping features, accurate 3‐D modeling is necessary. To this end, a novel 3‐D optoelectrical finite‐element model is developed to analyze the performance of ultrathin solar cells. The model is applied to the case of ultrathin (<500 nm) chalcogenide solar cells (copper indium gallium (di) selenide, CIGSe), rear‐passivated with nanostructured Al2 O3 to circumvent optical and electrical losses. It is found that such a nanopatterned dielectric passivation scheme enhances broadband light‐trapping with reduced rear‐surface recombination, resulting in an absolute power conversion efficiency enhancement of 3.9%, compared to cells without passivation structure. Overall, the work shows how 3‐D finite element modeling can aid in analyzing and developing new optical and electrical solar cell designs for ultrathin solar cells such as those based on chalcogenides and perovskites. Abstract : A novel 3‐D optoelectrical finite‐element model is presented to analyze the performance of ultrathin solar cells. Overall, the study shows how 3‐D finite element modeling can aid in analyzing and developing new optical and electrical solar cell designs for ultra‐thin solar cells such as those based on chalcogenides and perovskites.